EXPLORING THE KNOWLEDGE AND FEEDING PRACTICES OF STUNTING CHILDREN IN RURAL: A QUALITATIVE STUDY - Novianti, Siti; Lina, Nur; Gustaman, Rian Arie (UNG, 2024)
Prevalence of stunting in Indonesia is still major health problem. This study aimed to explore the feeding practices and knowledge of Indonesian mothers in feeding under-five children with malnutrition and the role of the government, health officers and health cadres in stunting prevention. This research conducted during the Covid-19 pandemic in Indonesia to determine the situation of the pandemic on feeding children. This qualitative study was conducted in the rural Tasikmalaya regency through 18 in-depth interviews with mothers (n=12), midwives (n=2) and health cadres (n=4). Data were analyzed using thematic analysis. Most of the participants had low education, most of the fathers worked as entrepreneurs with income above the minimum wage. The majority of the children were born with normal birth weight, while half of them were not exclusively breastfed, and most of the participants took iron pills during pregnancy. Feeding practices lack variety. Mother's knowledge about stunting is limited to only a superficial meaning. Stunting is still considered to be caused by short parental offspring, not a growth disorder related to poor nutrition. Despite the pandemic, fulfilling nutritional needs remains a mother's priority. Health workers and cadres have provided education about stunting and malnutrition, while the local government has made efforts to intervene but it is still not sufficient. The conclusion of this research is that mothers still lack knowledge and understanding about stunting, feeding practices are still not appropriate, and the pandemic situation has not changed the pattern of feeding practices for children.